Endothelium-Derived Relaxing Factor-Mediated Vasodilation in Mouse Mesenteric Vascular Beds - Hiroki Fujiwara; Yoshihiro Wake; Narumi Hashikawa-Hobara; Kento Makino; Shingo Takatori; Yoshito Zamami; Yoshihisa Kitamura; Hiromu Kawasaki (Elsevier, 2012)
The endothelium in rat mesenteric vascular beds has been demonstrated to regulate vascular tone by releasing mainly endothelium-derived hyperpolarizing factor (EDHF), which is involved in the activation of K+ channels and gap-junctions. However, it is unclear whether the endothelial system in mouse resistance arteries contributes to regulation of the vascular tone. The present study was designed to investigate the role of the endothelium using acetylcholine and A23187 (Ca2+ ionophore) in mesenteric vascular beds isolated from male C57BL/6 mice and perfused with Krebs solution to measure perfusion pressure. In preparations with active tone produced by methoxamine in the presence of guanethidine, injections of acetylcholine, A23187, and sodium nitroprusside (SNP) caused a concentration-dependent decrease in perfusion pressure due to vasodilation. The vasodilator responses to acetylcholine and A23187, but not SNP, were abolished by endothelium dysfunction and significantly inhibited by Nω-nitro-l-arginine methyl ester (nitric oxide synthase inhibitor) and tetraethylammonium (K+-channel inhibitor) but not glibenclamide (ATP-sensitive K+-channel inhibitor). Indomethacin (cyclooxygenase inhibitor) significantly blunted only A23187-induced vasodilation, while 18α-glycyrrhetinic acid (gap-junction inhibitor) attenuated only acetylcholine-induced vasodilation. These results suggest that the endothelium in mouse mesenteric arteries regulates vascular tone by prostanoids, EDHF, and partially by nitric oxide, different from the endothelium of rat mesenteric arteries. Keywords:: endothelium-dependent vasodilation, acetylcholine, Ca2+ ionophore, mesenteric vascular bed